ПОБУДОВА МОДЕЛЕЙ ОПТИМАЛЬНОЇ ВЗАЄМОДІЇ ДЖЕРЕЛ РОЗОСЕРЕДЖЕНОЇ ГЕНЕРАЦІЇ ТА СИСТЕМ АКУМУЛЮВАННЯ ЕНЕРГІЇ У МЕЖАХ MICROGRID СИСТЕМ - Дерев’янко, Д.Г.; Швірські, K. (Інститут електродинаміки НАН України, Київ, 2024)
The Problems of integration of DG and RES, as well as energy storage systems (ESS) in the Microgrid systems are investigated in this paper. It is proposed to consider Microgrid models of systems with different types of DG and RES (DER) within the framework of the SGAM architecture, and to distinguish three types of DG and ESS: " Non controllable DER (T1)", "Controllable DER (T2)" and "DER with storage systems (T3)" with further division into subtypes. This method makes it possible to display the multifaceted interaction of systems with DER and ESS within the framework of Microgrid systems. On the basis of the proposed mechanism, the formulation of the problem of optimal interaction of DG sources and ESS within the boundaries of Microgrid systems within the framework of game theory is formalized. An optimization procedure is proposed within the framework of a formalized game, which is based on mechanisms of dynamic pricing and allows to find the most optimal solutions for the game task. References 13, Figures 8, table 1.